PENGARUH PENGAWASAN, AKUNTABILITAS DAN TRANSPARANSI KEUANGAN TERHADAP KINERJA PEGAWAI (STUDI KASUS PADA DINAS PERHUBUNGAN KOTA TIDORE KEPULAUAN) - Benawan, Erick Try Putra; Saerang, David P. E.; Pontoh, Winston (GOING CONCERN : JURNAL RISET AKUNTANSI, 2018)
This research aims to know (1) the supervision of the financial influence on performance the employees, (2) Financial accountability against the influence of the performance of the employees, (3) to know how the transparency of financialmagainst the performance of the employees, and (4) the influence of supervision, accountability and transparency of financial performance against employees. This research was carried out at the Department of transportation of the city of Tidore Islands with a total population of as many as 30 people. The technique of sampling the Sampling technique using Saturated where the entire population was used as a sample to the population of less than 30 people. Types of data used in the study is quantitative data types and data sources while the primary data source. Method of data collection is done using documentation and detailed questionnaire. Data analysis techniques using multiple linear regression analysis with the help of the program SPSS version 16.00. The results of this study suggest that (1) the supervision of the influential Financial significantly to the performance of the employees of the Department of transportation of the city of Tidore Islands, (2) significant influential financialÂ accountability against staff performance Department of transportation city of Tidore Islands, (3) transparency of financial no effect significantly to the performance of the City Department of Transportation employee Tidore Islands. Keywords: Supervision, Accountability, Transparency, Â Employee Performance